A Case Study on the Evaluation of the Cheating - Bilgen Kıral (Anı Publishing, 2018)
The study was conducted to research the causes of the cheating of two students who entered the examination instead of each other, the changes that took place in their lives as a result of their punishment. A descriptive approach has been adopted in the research and it is a case study. For the study, the cheating statistics of the education faculty of a state university between 2000-2017 were examined. As a result of the researches conducted, the result was that the two students who participated in this study voluntarily participated in the interviews. The conclusion of the research was that the family of one of the students never knows the facts. They experienced some changes in their lives in terms of psychological, economic and educational. They don't have enough knowledge of punishments for cheating. Suggestions may be made to increase information about punishments that may result in cheating, such as having various shares on web sites, school boards, especially during examinations.